Designing and performance investigation of permanent magnet motor prototype for UTV electric drive train application - Muhammad Nur Yuniarto; Yoga Uta Nugraha; I Made Yulistya Negara; Dimas Anton Asfani; Indra Sidharta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The dynamic design specifications of a vehicle are used to define the required torque and speed of a permanent magnet motor. This is due to providing clear instructions on the intent, performance, and construction of a vehicle. Therefore, this study aims to determine an engineering design and prototyping process of a Permanent Magnet Motor, to be used as an electric powertrain in a Utility Vehicle. Based on being used in severe road condition (steep inclination and off road), the vehicle should be able to handle a 45° inclination with total payload of approximately 250 kg. Using a rear-wheel-drive traction, its weight should also be less than 1000 kg. Furthermore, the motor should be operated at a maximum battery voltage of 100 V. According to the requirements, the electric powertrain should further have the ability to deliver a torque of approximately 1600 Nm on both rear wheels. Using a finite element method to simulate performances, transmission was coupled to the motor in providing the required torque. In addition, the motor prototype was subsequently manufactured and tested using a dynamometer. The results showed that the motor produced 19.6 kW, 5600 RPM, and 75 Nm at 96 V. Therefore, the design and prototyping process of the motor satisfied all the required specification.